THE DEVELOPMENT OF A PROFESSIONAL LEARNING COMMUNITY MODEL INTEGRATED WITH PEER COACHING TO PROMOTE FUTURE SKILLS FOR EARLY CHILDHOOD AT NASAN MUNICIPAL KINDERGARTEN SCHOOL - Sathaporn, Sirinan (Journal of MCU Nakhondhat, 2025)
This research aimed to: 1) Develop and examine the quality of a model for building a professional learning community, 2) Study the effectiveness of the professional learning community model, and 3) Evaluate and validate the model. The target group was 8 early childhood teachers from Anuban Tessaban Na San School, selected through purposive sampling. The research instruments included document analysis forms, structured interview forms, group discussion topics, and a model appropriateness evaluation form. Data were analyzed using descriptive statistics-mean and standard deviation-and inferential statistics, specifically the paired t-test. The results showed that: 1) The developed model, titled "2O3K Model," aimed at building a professional learning community through peer coaching to enhance future skills for early childhood education at Anuban Tessaban Na San School. The model consisted of principles, objectives, essential implementation conditions, and a five-step process: Step 1-Organizational Learning (O), Step 2-Objectivity (O), Step 3-Knowledge Enhancement (K), Step 4-Knowledge-based Supervision (K), and Step 5-Knowledge Evaluation (K); 2) The effectiveness of the model was found to be high in all aspects, including pre- and post-implementation understanding, ability to promote future skills during implementation, supervisors' coaching abilities after implementation, and both teachers' and supervisors' opinions toward the model; and 3) The evaluation of the "2O3K Model" by experts indicated that all components of the model were rated at the highest level of appropriateness.